2014
DOI: 10.5152/akd.2014.5049
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-dose combination of losartan and hydrochlorothiazide significantly improves endothelial function in uncontrolled hypertension by low-dose amlodipine: A randomized study

Abstract: Objective: Flow-mediated dilation (FMD) and nitroglycerin-mediated dilation (NMD) in the brachial artery are well-known indices for evaluating endothelial function (ECF). The blood pressure-lowering effects of the combination of losartan (ARB) and low-dose hydrochlorothiazide (H: ARB-H; ARB, 50 mg and H, 12.5 mg) are useful. The aim of the present study was to examine whether the combination of losartan and low-dose hydrochlorothiazide could improve ECF. Methods: To investigate the effect of ARB-H on ECF in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The studies included in our meta-analysis were all RCTs, published until November 2020. The studies were conducted in Italy [ 12 19 ], Germany [ 20 ], China [ 21 26 ], Turkey [ 27 – 33 ], UK [ 34 ], Brazil [ 35 37 ], Greece [ 38 ], Denmark [ 39 ], Korea [ 40 45 ], Bulgaria [ 46 ], USA [ 47 ], Chile [ 48 ], and Japan [ 49 60 ]. A flow diagram depicting the inclusion process of these studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in our meta-analysis were all RCTs, published until November 2020. The studies were conducted in Italy [ 12 19 ], Germany [ 20 ], China [ 21 26 ], Turkey [ 27 – 33 ], UK [ 34 ], Brazil [ 35 37 ], Greece [ 38 ], Denmark [ 39 ], Korea [ 40 45 ], Bulgaria [ 46 ], USA [ 47 ], Chile [ 48 ], and Japan [ 49 60 ]. A flow diagram depicting the inclusion process of these studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Hypertension affects approximately 24.1% of men and 20.1% of women, corresponding to a total of 1.13 billion adults worldwide. 1 Many different antihypertensive drug combinations have been shown to be effective against this condition [2][3][4][5][6][7] ; however, poor medication persistence and adherence are common problems in hypertensive patients, partly because of complex treatment regimens and high pill burdens. 8,9 This results in sustained periods of uncontrolled hypertension, leading to disease progression and associated economic consequences.…”
Section: Introductionmentioning
confidence: 99%